Penerapan Media Video Animasi dalam Keterampilan Menulis Karangan Deskripsi Bahasa Jerman - Yunita Wulandari Palimbong; Syukur Saud; Nurming Saleh (Universitas Negeri Makassar, 2021)
Abstract. This research is a classroom action research conducted with 2 cycles. This study aims to determine the planning, process, and learning outcomes by using animated videos in the skills of writing descriptive essays in German for the XII grade students of SMAN 11 Makassar. This research data consists of two types, namely qualitative data and quantitative data. Qualitative data was obtained through observation, while quantitative data was obtained through writing skills tests in cycle I and cycle II. The data were analyzed using the percentage technique. The results showed that writing skills with the percentage of scores obtained by students in the first cycle reached 65.71 and the second cycle reached 78.28. These results indicate that the application of animated video learning media improves the writing skills of German language description essays for class XII students of SMA Negeri 11 Makassar.